Battery technology handbook - Kiehne, H. A. (Marcel Dekker, 2003)
A comprehensive guide to the fundamental theories, techniques and strategies utilized for battery operation and design, this handbook keeps specialists informed with the aid of new and revised chapters focusing on the safety, performance, quality and enhancement of batteries and battery systems.
Keywords: Electric batteries -- Handbooks, manuals, etc.; elektronické knihy; electronic books